“They just wanted to move on”: A qualitative study on the experiences of Black students in classroom discussions on race - Stewart, Ashley Marie (Frontiers in Education, 2023)
The current study used qualitative methods to explore what classroom conversations around race and social justice looked like for Black high school students and the role of technology in these conversations at a time where most students were engaging in hybrid or distance learning. Through semi-structured interviews, sixteen students recounted their experiences of talking about contemporary racial justice issues in school. Participants recalled experiences throughout their schooling in traditional classrooms as well as more recent experiences in the context of distance learning. Findings revealed that Black students take on much of the labor of educating their classmates and teachers about racial justice issues in class. They also highlighted the importance of safety when having these conversations. With regard to those discussions occurring in virtual settings, students described how technology promoted an environment in which Black students felt safer having these dialogues. Findings from this study emphasize the complex roles that Black students play in cultivating learning environments that raise the critical racial consciousness of everyone in the classroom, including teachers. Digital classrooms and spaces can also potentially serve as an environment in which Black students feel safe to fully explore and express their perspectives. These findings also further highlight the need to build the capacity of educators to facilitate conversations and hold space for all students to make sense of and cope when issues of racial injustice are at play and effecting the lives and mental health of students.